Предмет: Математика,
автор: parhomenkomarina98
[3(x -5)-1=6-2x
[3(x- -y)-7y=-4
Ответы
Автор ответа:
0
{ 3(x -5)-1=6-2x
{ 3(x- -y)-7y=-4
{ 3x - 15 - 1 = 6 - 2x
{ 3x - 3у - 7y = -4
{ 3x + 2х = 6 + 15 + 1
{ 3x - 10y = -4
{ 5х = 22
{ 3х - 10у = -4
{ х = 22/5
{ 10у = 3х + 4
х = 4,4
10у = 3 • 4,4 + 4
10у = 13,2 + 4
10у = 17,2
у = 17,2 : 10
у = 1,72
Ответ: х = 4,4; у = 1,72
{ 3(x- -y)-7y=-4
{ 3x - 15 - 1 = 6 - 2x
{ 3x - 3у - 7y = -4
{ 3x + 2х = 6 + 15 + 1
{ 3x - 10y = -4
{ 5х = 22
{ 3х - 10у = -4
{ х = 22/5
{ 10у = 3х + 4
х = 4,4
10у = 3 • 4,4 + 4
10у = 13,2 + 4
10у = 17,2
у = 17,2 : 10
у = 1,72
Ответ: х = 4,4; у = 1,72
Похожие вопросы
Предмет: Другие предметы,
автор: лол329
Предмет: Английский язык,
автор: 79092971981
Предмет: Русский язык,
автор: aiala
Предмет: Английский язык,
автор: СинийБатя
Предмет: Русский язык,
автор: cocles